GROWTH RESPONSE OF SETARIA GRASS (Setaria sphacelata) ON APPLICATION OF CUSCUS MANURE IN THE SECOND DEFOLIATION - Nauw, Sriani; Sawen, Diana; Nuhuyanan, Lamberthus; Junaidi, Muhammad (Pastura : Jurnal Ilmu Tumbuhan Pakan Ternak; Vol 11 No 1 (2021): Pastura Vol. 11 No. 1 Tahun 2021DO - 10.24843/Pastura.2021.v11.i01.p06, 2021)
This study aims to determine the response to the growth of setaria grass (Setaria sphacelata) on application cuscus manure from captivity in the second defoliation. The research was conducted for 3 months, located on Jl. Flamboyant B.18 Amban Manokwari, West Papua. The study was designed with a completely randomized design (CRD) with 3 treatments and 5 replications. The treatments given included: P0 = control (withoutfertilizer); P1 = cuscus animal manure based on bananafeed; and P2 = cuscus animal manure based on avocado feed. The results showed that the application of cuscus’ manure fertilizer based on banana and avocado feed had a significant effect on the growth of plant height, number of leaves and number of Setaria spachelata tillers. The best average plant height, number of leaves and number of tillers produced in the P1 treatment were 52.98 ± 2.34 cm, 74.63 ± 18.46 leaves, and 16.30 ± 4.97 tillers, respectively. The treatment of cuscus manure gave optimal results on the growth of Setaria grass. Keyword: Setaria sphacelata, organic fertilizer, growth